Research in non-university higher education institutions: The case of the Swiss Universities of Applied Sciences - Lepori, Benedetto (Higher education, 2008)
This paper presents the development of research in the Swiss non-university higher education sector and frames it in the debate on the organization of higher education systems in Western Europe and on the dynamics between university and non-university sector. It shows that, in the Swiss case, the applied research mandate has been used to differentiate these institutions from universities and that this endeavor has been to a large extent successful in technology, while it has been a source of major tensions in the other domains. I conclude that the development of research in the non-higher education leads to complex dynamics of convergence and of differentiation and that this process is strongly influenced by the specificities and differences between different subject domains.